2020
DOI: 10.3174/ajnr.a6345
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Hemorrhage after Successful Recanalization in Patients with Acute Ischemic Stroke: Improved Risk Stratification Using Dual-Energy CT Parenchymal Iodine Concentration Ratio Relative to the Superior Sagittal Sinus

Abstract: BACKGROUND AND PURPOSE: Brain parenchymal hyperdensity on postthrombectomy CT in patients with acute stroke can be due to hemorrhage and/or contrast staining. We aimed to determine whether iodine concentration within contrast-stained parenchyma compared with an internal reference in the superior sagittal sinus on dual-energy CT could predict subsequent intracerebral hemorrhage.MATERIALS AND METHODS: Seventy-one patients with small infarct cores (ASPECTS $ 7) and good endovascular recanalization (modified TICI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 31 publications
2
22
1
Order By: Relevance
“…This method was thought to account for variability in iodine concentration depending on factors such as patient size, cardiac output, renal function, and volume of contrast medium administered. 42 However, while contrast staining predicts intracranial hemorrhage, in another study it was not found to be associated with symptomatic hemorrhage or functional outcomes. 35…”
Section: Ischemic Strokementioning
confidence: 92%
See 1 more Smart Citation
“…This method was thought to account for variability in iodine concentration depending on factors such as patient size, cardiac output, renal function, and volume of contrast medium administered. 42 However, while contrast staining predicts intracranial hemorrhage, in another study it was not found to be associated with symptomatic hemorrhage or functional outcomes. 35…”
Section: Ischemic Strokementioning
confidence: 92%
“…This method was thought to account for variability in iodine concentration depending on factors such as patient size, cardiac output, renal function, and volume of contrast medium administered. 42 However, while contrast staining predicts intracranial hemorrhage, in another study it was not found to be associated with symptomatic hemorrhage or functional outcomes. 35 Postprocedural DECT may help to guide antiplatelet therapy in patients who have EVT and stenting of carotid occlusions to balance the risks of bleeding and stent thrombosis based on risk factors seen on DECT such as infarct size, contrast staining, and hemorrhage.…”
Section: Post-thrombectomymentioning
confidence: 92%
“…A study measuring relative iodine density between the superior sagittal sinus and the ischemic region in patients with contrast staining, demonstrated that a relative iodine value of 100% was associated with a 94.7% sensitivity, 43.4% specificity, and a likelihood ratio of 1.7 for HT. 23…”
Section: Non-contrast Ctmentioning
confidence: 99%
“…1 Parenchymal hyperdense lesions, commonly observed on brain computed tomography scans after EVT, are caused by ischemic disruption of the blood-brain barrier and may be seen with secondary contrast staining or hemorrhage. [2][3][4] Dual-energy computed tomography (DECT) can accurately differentiate hemorrhage from contrast staining, and parenchymal contrast staining has been associated with the development of future HT. 2-4 However, whether the predictability may be improved when both imaging and clinical markers are simultaneously considered and the imaging marker associated with HT volume remain unclear.Hence, we aimed to identify quantified markers for iodine extravasation on early DECT for the occurrence and volume of HT and investigate whether the simultaneous consideration of clinical markers could improve predictability.This single-center retrospective study included patients with acute ischemic stroke with large artery occlusion of the anterior circulation, who underwent EVT and DECT within 60 minutes after EVT between May 2019 and October 2020 (Supplementary Figure 1).…”
mentioning
confidence: 99%
“…The details of the study design and imaging analysis are described in the Supplementary methods and Supplementary results. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Briefly, the volume of interest (VOI) was manually drawn by two independent readers. The VOIs covered § Volume of iodine extravasation was defined as the voxel volume with an iodine concentration >0.7 mg/mL.…”
mentioning
confidence: 99%